Long‐Term Slowdown of Ocean Carbon Uptake by Alkalinity Dynamics. Issue 4 (13th February 2023) - Chikamoto, Megumi O.; DiNezio, Pedro; Lovenduski, Nicole
Abstract: Oceanic absorption of atmospheric carbon dioxide (CO2 ) is expected to slow down under increasing anthropogenic emissions; however, the driving mechanisms and rates of change remain uncertain, limiting our ability to project long‐term changes in climate. Using an Earth system simulation, we show that the uptake of anthropogenic carbon will slow in the next three centuries via reductions in surface alkalinity. Warming and associated changes in precipitation and evaporation intensify density stratification of the upper ocean, inhibiting the transport of alkaline water from the deep. The effect of these changes is amplified threefold by reduced carbonate buffering, making alkalinity a dominant control on CO2 uptake on multi‐century timescales. Our simulation reveals a previously unknown alkalinity‐climate feedback loop, amplifying multi‐century warming under high emission trajectories. Plain Language Summary: Over the past century, humans have been burning fossil fuels and adding extra carbon dioxide to the atmosphere. The ocean has been doing us a big favor by absorbing some of this carbon dioxide, lowering the amount of global warming that occurs. Our study shows that the ocean will begin to lose its ability to absorb carbon dioxide beyond the year 2100, leaving more fossil‐derived carbon in the atmosphere and leading to additional global warming. Our study describes a previously undiscovered mechanism for the slowdown in ocean carbon absorption, where changes in rainfall and warming affect ocean currents that, in turn, change the chemistry of the ocean surface. Key Points: Oceanic uptake of carbon could slow in upcoming centuries through previously unidentified alkalinity‐climate feedback Reduced upwelling and carbonate buffer enhance the influence of alkalinity on the increase in surface ocean carbon dioxide Reductions in surface alkalinity will reduce the rate of carbon uptake on multi‐century timescales